Spark Plasma Sintering of Commercial Zirconium Carbide Powders: Densification Behavior and Mechanical Properties - Xialu Wei; Back C. Christina; Izhvanov O. Oleg; Grigorjev E. G. Evgeny Grigorjevich; Khasanov O. L. Oleg Leonidovich; Haines Ch. D. Christopher; Olevsky E. A. Evgeny Aleksandrovich (Manufacturing Processes and Systems, 2015)
Title screen